Zdravstvena nega novorojenca s prirojeno srčno napako - Urh, Irma (Obzornik zdravstvene nege, 1999)
The article presents nursing care of a new-borninfant with congenital heart disease based on the model of Virginia Henderson and the theory of needs of Abraham G. Maslow. Only those life activities which belong to the very top of the hierarchy of needs of a new-born infant with congenital heart disease, arepresented. Congenital heart disease often causes breathing difficulties manifested with dispnea. An early symptom of heart failure is liquid retentionwhich represents a decline in health status. Skin of a new born infant is thin and fragile, body temperature is low and feeding problems frequent. Because of pain, sleep and rest are often disturbed. The nurse has to develop her observation abilities to notice symptoms of heart failure in time and to take proper and timely measures. For the work with parents, knowledge from counseling techniques and health education are required.
Keywords: Heart defects, congenital; Infant care; Infant, newborn; kardiologija; nega bolnika; novorojenčki; Nursing; Nursing care; Nursing process; Nursing theory; Patient care planning; prirojene hibe; srčne hibe